Novel Avulaviruses in Penguins, Antarctica - Víctor Neira; Rodrigo Tapia; Claudio Verdugo; Gonzalo Barriga; Sunil Mor; Terry Fei Fan Ng; Victoria García; José Del Río; Pedro Rodrigues; Cristóbal Briceño; Rafael A. Medina; Daniel González-Acuña (Emerging Infectious Diseases, 2017)
We identified 3 novel and distinct avulaviruses from Gentoo penguins sampled in Antarctica. We isolated these viruses and sequenced their complete genomes; serologic assays demonstrated that the viruses do not have cross-reactivity between them. Our findings suggest that these 3 new viruses represent members of 3 novel avulavirus species.